(untitled) (Reflection and Critique Law Magazine, 2025)
Since before the Second Reign, internal and external pressures from different groups of society marked the fight against slavery. In addition to the persistent disobedience of the slaves, which denied the status of slave through violence against their masters and masters’ property, escapes and even suicide, others imperial society actors also stood in favor of the abolitionist cause: as the militaries and republicans (the latter was composed of independent professionals). However, it is undeniable that without the external pressure promoted by the British Empire, the slave system would have lasted much longer. English intervention was marked by versions and speeches and resulted in the Eusébio de Queirós Law, whose existence and validity can only be understood when the politicians’ pragmatic decisions of both empires are added to the political currents of the time.